Extraction and characterization of Bioactive Compounds from Koshim ( Dovyalis Abyssinica Warb) Fruits Juices Using Uv-vis Spectrophotometry - Gerboshe Kenea (ASTU, 2017)
The purpose of this study was to develop a simple method to extract and analyze the physical (optical) properties of bioactive compounds for solvent extraction from koshim (Dovyalis Abyssinica Warb) fruits juice using Uv-vis spectrophotometer. The solvent method was used for the extraction of bioactive compounds from Dovyalis fruits juice. The methanol and ethanol with hexane and tri-mixtures (hexane/acetone/ethanol) solvents were tested and tri-mixtures was found to be the best solvent for extraction, resulting in the identified major peaks with Uv-vis and high content of phenolic (anthocy- anins or flavonoids) (3.796+0.594mg/100g)) and carotenoids (0.618+0.289mg/100g (in fresh juice) and 2.440+0.161mg/100g (in dried)) juice. Moreover, with ethanol extraction, there was a long, red (pell-yellow) spectacular solution mixture of carotenoids and phenolic bioactive compounds identified or observed without further purification. In case of the influence of the blending time (in 1, 3, and 5-minutes) on extraction yields, increasing the blending time from 1-3 resulted in an increase of extraction efficiency and 3-minute was an optimum time for maximum efficiency, but an increase of blending time from 4-5 minutes progressively there was a degradation and isomerization of bioactive compounds as a result of oxidative reduction process, resulted in decrease of extraction efficiency.